1997
DOI: 10.1002/(sici)1096-8652(199709)56:1<37::aid-ajh8>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative utility of diagnostic bone-marrow components: A 10-year study

Abstract: Ten years of cumulative experience represented by 4,902 consecutive diagnostic bonemarrow examinations at a tertiary care and referral center were reviewed to assess the value of specific components. While it has been shown previously that the information obtained from each component is generally complementary, the inclusion of some or all components may vary between institutions. The components studied included aspirate smears, clot sections, biopsy cores, and touch imprints of biopsy and clot sections. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Many studies done previously showed that BMB was a better procedure for detecting metastatic tumour. [7][8][9], Only 50% cases showed a positive correlation in our study, which is in agreement with studies by Atac et al [10] where he studied 39 cases and each positive BMB was also positive by BMA. In our study the metastasis were mostly adenocarcinomas 3/6 (primary from gastric carcinoma), 1/6 small cell carcinoma where the primary was unidentified, 2/6 cases of poorly differentiated carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies done previously showed that BMB was a better procedure for detecting metastatic tumour. [7][8][9], Only 50% cases showed a positive correlation in our study, which is in agreement with studies by Atac et al [10] where he studied 39 cases and each positive BMB was also positive by BMA. In our study the metastasis were mostly adenocarcinomas 3/6 (primary from gastric carcinoma), 1/6 small cell carcinoma where the primary was unidentified, 2/6 cases of poorly differentiated carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…An adequate bone marrow core biopsy adds this important information. Bone marrow biopsy is essential in case of 'dry tap' or 'blood tap' (9) Hence, we attempted to correlate both these parameters to arrive at a more conclusive final diagnosis. …”
Section: Introductionmentioning
confidence: 99%
“…During the bone marrow examination, bone marrow particles are aspirated and spread on slides, and a core of bone and marrow (trephine biopsy) is also obtained. The bone marrow aspirate preparations are valuable for differential cell counts and the evaluation of individual cell morphology, while the trephine biopsy is preferred for the evaluation of marrow cellularity, accurate determination of the number of megakaryocytes, and the detection of focal lesions such as lymphoma, granulomas, and metastatic carcinoma (2)(3)(4)(5)(6)(7)(8). Since the aspirate and biopsy provide complementary information, both specimens are routinely obtained.…”
Section: Introductionmentioning
confidence: 99%